2021
DOI: 10.2147/ott.s297263
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Prediction Model for Locally Advanced Rectal Cancer Following Neoadjuvant Chemoradiotherapy Based on Pretreatment Tumor-Infiltrating Macrophage-Associated Biomarkers

Abstract: Purpose To assess the value of macrophage-related biomarkers (CD163, CD68, MCSF, and CCL2) for predicting the response to neo-chemoradiotherapy (NCRT) and the prognosis of locally advanced rectal cancer (LARC). Methods We enrolled 191 patients who underwent neoadjuvant chemoradiotherapy and radical resection between 2011 and 2015. Tumor tissues were collected before NCRT with a colonoscope and post-surgery and were subjected to immunohistochemical analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Nevertheless, a study by Kitagawa et al on pre-treatment biopsies from 275 patients with rectal cancer treated with neoadjuvant CRT showed that low CD68+ macrophage counts were more frequently recorded in tumors that poorly responded to CRT [87]. Similar findings were reported by Liu et al in a series of 191 rectal cancer patients treated with preoperative CRT [88] (Table 1). As tumor-associated macrophages (TAMs) can be polarized towards M1-effector or M2-immunosuppressive phenotype, their role in response to RT and prognosis may be differentially driven by the TAM-subtype prevalence [89].…”
Section: The Cd47-sirpα 'Don't Eat Me' Pathwaysupporting
confidence: 65%
“…Nevertheless, a study by Kitagawa et al on pre-treatment biopsies from 275 patients with rectal cancer treated with neoadjuvant CRT showed that low CD68+ macrophage counts were more frequently recorded in tumors that poorly responded to CRT [87]. Similar findings were reported by Liu et al in a series of 191 rectal cancer patients treated with preoperative CRT [88] (Table 1). As tumor-associated macrophages (TAMs) can be polarized towards M1-effector or M2-immunosuppressive phenotype, their role in response to RT and prognosis may be differentially driven by the TAM-subtype prevalence [89].…”
Section: The Cd47-sirpα 'Don't Eat Me' Pathwaysupporting
confidence: 65%
“…Adequately predicting the response to neoadjuvant chemoradiotherapy (nCRT) in rectal cancer represents a key factor in order to achieve a fully personalized treatment approach, especially in the case of locally advanced disease presentation, which constitute a well-established indication for radiation therapy [127]. The identification of biomarkers able to predict patients' outcomes (i.e., response to nCRT) currently represents a priority in the radiotherapy research landscape, and imaging-derived response predictors are a topic of active investigation [128][129][130][131][132][133].…”
Section: Texture Analysis In Neoadjuvant Radiotherapy-a Focus On Rectal Cancermentioning
confidence: 99%
“…It appears that TAMs affect the tumor microenvironment by suppressing cytotoxic T lymphocyte responses [ 99 ]. In a study of 191 patients with LARC, macrophage-associated biomarkers CD163, CD68, macrophage colony-stimulating factor (MCSF) and C-C chemokine ligand 2 (CCL2) in pre-nCRT and post-surgery tumor tissue were found to be higher in patients who were associated with a poorer response to nCRT and lower in patients with a complete pathological response [ 100 ]. A study of 85 patients revealed that CD26 overexpression in rectal cancer cells was correlated with a poor pathological response to CRT.…”
Section: Resultsmentioning
confidence: 99%